2014
DOI: 10.1038/srep06423
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of post-earthquake depressive and anxiety symptoms: a longitudinal resting-state fMRI study

Abstract: Neurobiological markers of stress symptom progression for healthy survivors from a disaster (e.g., an earthquake) would greatly help with early intervention to prevent the development of stress-related disorders. However, the relationship between the neurobiological alterations and the symptom progression over time is unclear. Here, we examined 44 healthy survivors of the Wenchuan earthquake in China in a longitudinal resting-state fMRI study to observe the alterations of brain functions related to depressive … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
13
0
2

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(18 citation statements)
references
References 42 publications
3
13
0
2
Order By: Relevance
“…Each nodal mean time series was corrected by regressing out head motion. Recent studies have regressed out global signal in functional connectivity analysis111213, but global signal regression could mathematically create artefactual negative correlations. However, this technique can be used to effectively reduce motion-related artifacts that cannot be removed by a variety of motion-based regressors12 and is considered to be a processing maneuver that facilitates the evaluation of underlying neurophysiological relationships11, making the interpretation of the results with global signal regression more reliable.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Each nodal mean time series was corrected by regressing out head motion. Recent studies have regressed out global signal in functional connectivity analysis111213, but global signal regression could mathematically create artefactual negative correlations. However, this technique can be used to effectively reduce motion-related artifacts that cannot be removed by a variety of motion-based regressors12 and is considered to be a processing maneuver that facilitates the evaluation of underlying neurophysiological relationships11, making the interpretation of the results with global signal regression more reliable.…”
Section: Methodsmentioning
confidence: 99%
“…All subjects were divided into non-overlapped training and testing samples. Using the feature vectors, we applied a linear support vector machine (SVM) approach to perform classifier training and generalization testing13. For the classifier training, feature vectors of the training samples were used to train three linear SVM classifiers based on the one-versus-rest method (e.g., VS/UWS vs. MCS and controls)25.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Aberrant connectivity between these regions has been observed in various psychiatric disorders. Much of the current literature suggests that lower connectivity between the amygdala and the prefrontal cortex indexes higher levels of anxiety in both healthy controls (Coombs et al, 2014;Kim et al, 2011;Loewenstern et al, 2014;Long et al, 2014) and patients (Dodhia et al, 2014;Keutmann et al, 2014). This lower connectivity was also observed in major depression (MDD) (Lui et al, 2011;Tang et al, 2013), BD (Anand et al, 2009;Chepenik et al, 2010) and obsessive-compulsive disorder (OCD) (Gottlich et al, 2014).…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…Imaging studies have demonstrated that traumatic events alter functional connectivity of the prefrontal cortex in humans (Krause-Utz et al, 2014; Lanius et al, 2010;Long et al, 2014;van Wingen et al, 2012) and rodents (Henckens et al, 2015;Liang et al, 2014), but synaptic process underlying such changes remains largely unexplored. To that end, we examined OF-induced synaptic adaptations in PCs in dmPFC layer V, which are one of the major outputs of dmPFC.…”
Section: Discussionmentioning
confidence: 99%